Piecing together our woodlands – Interview with Suzanne Prober - McDonald, Tein; Prober, S. (Wiley-Blackwell Publishing Ltd, 2018)
© 2018 Ecological Society of Australia and John Wiley & Sons Australia, Ltd Over nearly three decades, Suzanne Prober has played a pivotal role in shifting research in Australian agricultural landscapes to include a focus on native woodlands, and to examine ways woodland conservation can co-exist with production, contributing to new models for conservation within multi-use landscapes.